Chapter 1 History and development of mental health law - Kelly, Brendan D. (Taylor & Francis, 2024)
Mental health legislation has a lengthy history in most societies. Legislation commonly outlines the circumstances under which treatment without consent is permitted in psychiatric facilities. While the history of mental health legislation varies somewhat across jurisdictions, many saw significant expansions in mental health law during the nineteenth century, especially with the establishment of large public 'mental hospitals'. These institutions generally declined during the twentieth century as treatments improved, societies became less tolerant of institutions, and bodies such as the United Nations increased their emphasis on human rights. This chapter summarises the history of mental illness and relevant legislation, early efforts to control people deemed 'mentally ill', the emergence and decline of mental hospitals, recent emphasis on human rights, and likely future developments. While this chapter uses the examples of Ireland (a high-income country in the Global North) and India (a lower middle-income country in the Global South), many countries remain under-represented in both the historiography and general literature. This chapter concludes that it is essential that mental health laws are just and fair, but that legislation has always been part of a broader social system of care which has commonly failed people with mental illness. We can and must do better.